Clinical utility of urine specific gravity, electrical conductivity, and color as on‐farm methods for evaluating urine concentration in dairy cattle. (25th April 2019) - Megahed, Ameer A.; Grünberg, Walter; Constable, Peter D.
Abstract: Background: Urine concentration (UC) provides clinically useful information concerning hydration status and renal function of animals. Objectives: To characterize the clinical performance of urine specific gravity measured by optical refractometry (USG‐R ) or Multistix‐SG urine reagent dipstick (USG‐D ), urine electrical conductivity using an OAKTON Con 6 conductivity handheld meter (UEC ), urine color (UColor ) using a custom‐designed 8‐point color chart, and urine creatinine concentration (UCreat ) for assessing UC in dairy cattle. Animals: 20 periparturient Holstein‐Friesian cows. Methods: Urine was obtained by perineal stimulation or urethral catheterization and urine osmolality (UOsm, reference method), USG‐R, USG‐D, UEC, UColor, and UCreat determined. Diagnostic test performance was evaluated using Spearman's rho and logistic regression to determine the area under the receiver operating curve (AUC) and optimal cut point for diagnosing hypohydration (UOsm ≥800 mOsm/kg). P < .05 was considered significant. Results: The best performing test for diagnosing hypohydration was USG‐R (AUC = 0.90) at an optimal cut point ≥1.030. The second‐best performing test was UEC (AUC = 0.82) at a cut point of ≥23.7 mS/cm, followed by UCreat (AUC = 0.76) at a cut point of ≥95.3 mg/dL, and UColor (AUC = 0.74) at a cut point of ≥4 on an 8‐point scale. Urine specific gravity measured by dipstick performed poorly (AUC = 0.63). Conclusions and Clinical Importance: USG‐R and UEC provide practical and sufficiently accurate methods for measuring UC in dairy cattle. Urine color had moderate clinical utility as a no‐cost cow‐side method for assessing UC, whereas dipstick refractometry is not recommended for assessing UC.